Fulfilling Communal Rights through the Implementation of the Second Principle of Pancasila towards the Regulation on Agrarian Reform - Kartika Winkar Setya; Abdul Aziz Nasihuddin; Izawati Wook (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2023)
Fulfilling communal rights to customary lands has still become an unresolved polemic. As a country adhering to Pancasila ideology, all laws and regulations should embody in Pancasila, including regulation on Agrarian Reform. This research aimed to figure out the reduction of values found in the 2nd principle of Pancasila against the Presidential Regulation Number 86 Year 2018 concerning Agrarian Reform in the context of fulfilling communal rights of indigenous peoples to customary lands. The research used a normative-juridical method with both statutory and analytical approaches. This research specifically examined and analyzed the reduction of values in the second principles of Pancasila toward the regulation of agrarian reform in Indonesia. The data sources were in the form of secondary data to obtain objective research results including primary, secondary, and tertiary legal materials obtained through documents and literatures. The collected data were then qualitatively analyzed and presented in the forms of narrative text. By implementing the second principle of Pancasila, the communal rights to customary lands are fulfilled in Agrarian Reform and become the basis to strengthen the position of indigenous peoples in national legal system.